Evaluating university attributes and their influence on students' attitudes: The mediating role of social responsibility communication - Mokhtar Elareshi; Samar Ben Romdhane; Wasim Ahmed (Administrative Sciences, 2024)
Understanding the salience of university attributes assists institutions in developing messaging strategies (using social responsibility communication (SRC) initiatives) to meet students' needs. This research examines which university attributes hold the greatest significance and importance for students selecting a higher-education institution (HEI), focusing on the role of SRC as a mediator. An online survey with a sample of 120 university students was conducted. The findings indicate that the cost of education, employment opportunities, physical aspects and resources, and university image are important attributes. The study shows that while university attributes significantly predict SRC (Model 1), neither university attributes nor SRC significantly predicts student attitudes (Models 2 and 3). The mediation analysis confirms that SRC does not mediate the relationship between university attributes and students' attitudes, suggesting that factors other than university attributes and SRC may play a more critical role in shaping students' attitudes.
Keywords: 350; HEIs; organisational communication; social responsibility communication (SRC); students' attitudes; universities